Manganese-based nanoadjuvants for enhancement of immune effect of DNA vaccines - Ma, Qiang; Mu, Yongxu; Gong, Lidong; Zhu, Chuanda; Di, Shiming; Cheng, Ming; Gao, Jinming; Shi, Jihai; Zhang, Liang (Frontiers in Bioengineering and Biotechnology, 2022)
As a highly pathogenic avian influenza virus, Influenza A (H5N1) has been reported to infect humans, posing a major threat to both poultry industry and public health. It is an urgent need to develop a kind of effective vaccine to prevent death and reduce the incidence rate of H5N1 avian influenza. Compared with traditional inactivated or attenuated vaccines, deoxyribonucleic (DNA) vaccines have the advantages of continuously expressing plasmid-encoded antigens and inducing humoral and cellular immunity. However, the immune effect of DNA vaccines are limited to its poor immunogenicity. Using of nanoadjuvants with DNA vaccines holds a great promise to increase the transfection efficiency and immunogenicity of DNA vaccines. In this study, we developed a nano co-delivery system with a manganese-based liposome as adjuvant for delivery of a DNA vaccine. This system has been found to protect DNA vaccine, enhance phagocytosis as well as promote activation of antigen-presenting cells (APCs) and immune cells in draining lymph nodes. In addition, the effect of this nanovaccine has been evaluated in mouse models. The nanovaccine can induce the host to produce highly effective hemagglutination inhibition antibody (HI) and IgG antibody, and simultaneously activate the humoral and cellular immunity of the host. Overall, this strategy opens up a new prospect for manganese nanoadjuvants in increasing the immunogenicity of DNA vaccines.